Information Literacy Analisys of Primary School Students - Farida Nur Kumala; Dwi Agus Setiawan; Nury Yuniasih; Dyah Triwahyuningtyas; Prihatin Sulistyowati (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
The purpose of this study was to analyze information literacy of primary school students in Malang. 725 students of fifth grade were involved in this study as respondents. This study used a measurement test sheet of students’ information literacy based on the indicators of information literacy suggested by UNESCO and OECD consisting of 6 indicators. The data from the literacy test were then analyzed using descriptive quantitative analysis technique. Based on the average value of each indicator, it can be concluded that the average information literacy of the students in 18 primary schools in Malang is 5.09 categorized as sufficient category. Information literacy is useful for children in knowing, understanding and filtering the information obtained so that children can interpret and use information wisely.